PSII-22 Comparison of the meat quality traits of crossbred pigs and the Large Black pigs. (5th December 2019) - Wang, Yongjie; Thakali, Keshari; Shelby, Sarah; Apple, Jason; Huang, Yan
Abstract: The purpose of this study was to compare the meat quality and genomic differences between cross-bred commercial pig (CP) and domestic Large Black pig (BP). Seven cross-bred commercial pigs and eight British Large Black pigs were assigned to CP group and BP group, with initial mean body weights of 18.82±1.412 kg for CP group and 23.31±1.935 kg for BP group, P = 0.061, and fed ad libitum. The final BW of the CP at d101 was similar to the BP (130.0±8.16 kg vs. 121.1±2.80 kg, P = 0.132). However, the BP group took 108 days to reach the final BW. The ADG in the CP was higher than BP (1.102±0.0599 kg vs. 0.905±0.0138 kg, P = 0.003). The hot carcass weight of CP was higher (P < 0.01) than BP, but the backfat of BP was higher (P < 0.01) than CP. The a* value of CP was higher (P < 0.05) than BP, and the c* value of CP was tended to be higher (P < 0.10) than BP. However, the h value of BP was higher (P < 0.05) than CP. The longissimus dorsi muscle fat content of BP was higher (P < 0.05) than CP. For the fatty acid composition, the SFA and MUFA of BP were higher (P < 0.05) than CP, but the PUFA of CP was higher (P < 0.05) than BP. The metmyoglobin content of CP was tended to be higher (P < 0.10) than BP. For the meat metabolism, the oxygen consumption of longissimus dorsi muscle of BP was higher (P < 0.01) than CP. The RNA-Seq data showed that the expression of the genes related to lipid metabolism is higher in BP (fold change > 3, P < 0.05). To conclude, BP has higher meat quality, while CP has its advantages in growth performance. And the differences between these two breeds may due to the genomic diversity.